Preparation of silver-nanoparticle-loaded C60-ethylenediamine adduct microparticles and their application to photoelectric conversion. (4th June 2021) - Matsuoka, Ken-ichi; Banya, Shoto; Hosoi, Ippei; Koyama, Natsuki; Suzuki, Kazumasa; Jeyadevan, Balachandran; Oku, Takeo; Fujita, Katsuhiko; Yamada, Sunao; Akiyama, Tsuyoshi
Abstract: We report here new types of suprastructure products consisting of C60 -ethylenediamine microparticles and silver nanoparticles that were loaded onto the surfaces of the microparticles by electrostatic adsorption. The suprastructure products could be deposited on the surface of an indium tin oxide electrode by electrostatic deposition. These modified electrodes generated cathodic photocurrents in the presence of ascorbic acid and oxygen. The photocurrent generation behavior implies an ensemble of the electron-transfer processes of silver-nanoparticle-mediated electron transfer acting in the cathodic direction and plasmon-induced charge separation acting in the anodic direction.